A Quantitative Analysis of Chromium and Zinc in Water and Raw Milk in Chittagong, Bangladesh - Akther, S.; Shahriar, S. M. S.; Alam, M. K.; Zakir, H. M. (Journal of Scientific Research, 2016)
The concentration of selected heavy metals (chromium and zinc) was detected and estimated in water and raw milk collected from Chittagong City of Bangladesh. A total of 25 water samples and 20 raw milk samples were collected from different farms situated in 10 locations of Chittagong, Bangladesh. Chromium content in water was obtained in the range from 0.2 µg/L to 13 µg/L. The highest level of chromium content in water was 13.068 µg/L. The content of chromium in raw milk was obtained in the range from 2 µg/L to 17 µg/L. The highest level of chromium in milk was 17.062 µg/L. Chromium concentrations in water and milk were below the maximum allowed limit.  The concentration of zinc in water was in the range from 0.01 mg/L to 1 mg/L. The highest level of zinc in water was 1.024 mg/L. The concentration of zinc in raw milk was in the range from 0.6 mg/L to 0.9 mg/L. The highest concentration of zinc in water was 1.024 mg/L which is around the toxicological guidance value of zinc.